2014
DOI: 10.18632/aging.100673
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between ROS dependent DNA damage, mitochondria and p38 MAPK underlies senescence of human adult stem cells

Abstract: Human endometrium-derived mesenchymal stem cells (hMESCs) enter the premature senescence under sublethal oxidative stress, however underlying mechanism remains unknown. Here, we showed that exogenous H2O2 induces a rapid phosphorylation and co-localization of ATM, H2A.X, 53BP1 leading to DNA damage response (DDR) activation. DDR was accompanied with nuclear translocation of p-p53 followed by up-regulation of p21Waf1 and the permanent hypophosphorylation of pRb. Additionally, the increased p38MAPK/MAPKAPK-2 act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(146 citation statements)
references
References 53 publications
5
140
1
Order By: Relevance
“…In cellular arrest, DDR induced the activation of p53 and upregulated p21 to inactivate pRb. Moreover, the pharmacological inhibition of the p38 MAPK activation abrogated the hydrogen peroxide-induced cell enlargement and flatten morphology, and it is associated with the regulation of mitochondrial ROS production [15]. Although senescent MSCs remain alive, the loss of MSC function with self-renewal and proliferation capacity leads to undergoing apoptosis or senescence.…”
Section: Ros Oxidative Stress and Cellular Signaling In Mscs Agingmentioning
confidence: 99%
“…In cellular arrest, DDR induced the activation of p53 and upregulated p21 to inactivate pRb. Moreover, the pharmacological inhibition of the p38 MAPK activation abrogated the hydrogen peroxide-induced cell enlargement and flatten morphology, and it is associated with the regulation of mitochondrial ROS production [15]. Although senescent MSCs remain alive, the loss of MSC function with self-renewal and proliferation capacity leads to undergoing apoptosis or senescence.…”
Section: Ros Oxidative Stress and Cellular Signaling In Mscs Agingmentioning
confidence: 99%
“…In human mesenchyme stem cells, the SakA-homologous MAPK p38 mediates increased mitochondrial activity in an MK2-dependent manner, higher ROS levels, a persistent DNA damage response, DNA double-strand breaks (DSBs), and activation of the ATM pathway. This feedback loop seems necessary to stop the cell cycle and drive cells into senescence (75). Mitochondrial ROS are produced by partial O 2 reduction in the respiratory chain or by damage and loss of membrane potential (76,77).…”
Section: Figmentioning
confidence: 99%
“…Therefore, our results and data from other researchers indicate that the initiation of markedly adverse effects in astrocytes requires a dose rang of TCDD that is much higher than that triggering AhR activation. Mounting evidences have indicated that ROS were key players in stress-induced premature senescence (Borodkina et al, 2014;Lee and Bae, 2014;Liu et al, 2014). The generation of ROS leads to significant accumulation of cell cycle inhibitors, including Rb, p21 and p27 proteins, and oxidative DNA damage, all of which are important features of cell senescence (Stockl et al, 2006;Liu et al, 2014;Wan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%